Examining secondary talented and gifted and agricultural education experiences relative to college major and career choice - Gallagher, Darcie E. (Kansas State University, 2019)
The purpose of this study was to describe the role of secondary talented and gifted and agricultural education experiences in college major and related career choice. This descriptive study sought out how institutions may go about recruiting and training individuals based upon characteristic and involvement information, perceptions of past academic experiences, and expectations of a future career. Results indicated that there is not a direct correlation between talented and gifted program involvement with a major and or career choice in agriculture, food, and natural resources, but there is potential to reach this dynamic group.
Keywords: Talented and Gifted; Agricultural Education; Career choice; College major